2017
DOI: 10.1016/j.enbuild.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating energy consumption saving from translucent concrete building envelope

Abstract: The translucent concrete (TC) as a building envelope can offset some lighting energy that is consumed within a room in an office. It is constructed from concrete panels which are functionalized by embedding optical fibers during the manufacturing phase to transmit sunlight. From preliminary results, a volumetric fiber ratio of 6% used in the TC panel leads to savings in lighting energy by around 50%. The utility of panels is enhanced if it reduces the heating and cooling requirements of the office room. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Photocatalysis has attracted researchers' interest due to its potential application in degradation of organic compounds for wastewater treatment, water splitting to produce high purity hydrogen, solar panels, and so on. [1][2][3][4] Several photocatalytic semiconductor materials, for instance ZnO and TiO 2 , have been widely used in degradation of organic compounds, nevertheless, most photocatalysts are faced with two problem: low efficiency under visible-light irradiation and difficult recycling of photocatalysts aer use. Thus, development of magnetic and highly efficient visible-light-driven photocatalysts has become an appealing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has attracted researchers' interest due to its potential application in degradation of organic compounds for wastewater treatment, water splitting to produce high purity hydrogen, solar panels, and so on. [1][2][3][4] Several photocatalytic semiconductor materials, for instance ZnO and TiO 2 , have been widely used in degradation of organic compounds, nevertheless, most photocatalysts are faced with two problem: low efficiency under visible-light irradiation and difficult recycling of photocatalysts aer use. Thus, development of magnetic and highly efficient visible-light-driven photocatalysts has become an appealing challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Ahuja et al [18] evaluated the monetary savings in energy consumption for heating, cooling and lighting of an interesting translucent concrete wall system in Berkeley. Unfortunately the reference was not a realistic scenario with a standard window wall but a completely opaque room.…”
Section: Methodsmentioning
confidence: 99%
“…It consisted of a structural TCP consisting mainly of two layers: (1) Layer A was RC with embedded symmetric CPCs, which are nonimaging concentrators (Winston 1974), to concentrate maximum natural sunlight from the outside in a geometrical manner without mechanizing the panel, and (2) Layer B was RC with embedded OFs as a structural subsystem to act as a conduit for the natural sunlight from the outside to the interior space, which turns the TCP into a translucent construction solution for the opaque part of the building envelope. In addition, the TCP integrated two concepts: (1) Another form of TCP was presented in Ahuja and Mosalam (2017), showing that the proposed construction solution provided energy savings of approximately 20% of the energy cost, and (2) other studies (Ahuja et al 2015a, b) have shown that the TCP through the OFs had daylight diffusion properties. The TCP was viewed as a novel wall technology with the property to transform an energy liability to an energy source providing daylight.…”
Section: Proposed Building-envelope Solutionmentioning
confidence: 97%
“…Little or no research has been conducted to quantify this potential or to compare the performance of OFs with other light-transmitting materials. An exception is the computational studies by Ahuja et al (2015a, b) and Ahuja and Mosalam (2017). There is usually an excess of sunlight outdoors compared to the indoor lighting required in most buildings such as commercial buildings, apartments, and public buildings.…”
Section: Introductionmentioning
confidence: 99%